Religious and essential aspects of reproduction in Islam - Orbanová, Eva (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2019)
The phenomenon of genealogical reproduction has long been subjected to a religious reflection of the respective part of the world. Consequently, this religious impact on the biological and reproductive sphere of human existence determined not only the life and lifestyle of a believer, but it has also connected him with the particular religious community. Islam, regarding its historical development, has its own specific reproductive rules. The article aims to analyze the essential aspects of reproduction resulting implicit in the sacred books of Islamic religion. Through the prism of personality, the author tries to recreate the moments that in a modified form reflect the family practice of the Islamic community